URGENSI KETERAMPILAN BERADAPTASI DAN FLEKSIBILITAS SISWA DALAM MENGHADAPI PERUBAHAN SOSIAL - Sekar Najwa Sal Sabila; Ishmatun Nabila; Alfan Nurngain (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Social change driven by globalization, digitalization, and modernization has significantly impacted students' lives in both academic and social aspects. These conditions require students to possess adaptability and flexibility skills to effectively cope with rapid and dynamic changes. This article aims to examine the concept of adaptability and flexibility skills in education, analyze the impact of social change on students' lives, and identify strategies for strengthening students' adaptive capacities. The study employs a library research method by reviewing various relevant scholarly sources related to social change, 21st-century education, and student skill development. The findings indicate that adaptability and flexibility are essential competencies that enable students to adjust to environmental changes, technological advancements, and increasingly complex educational demands. Social change provides positive impacts, such as easier access to information, broader perspectives, and the development of 21st-century skills. However, it also presents challenges, including information overload, shifts in social interaction patterns, and increasing competency demands. Strengthening adaptability and flexibility can be achieved through adaptive learning approaches, the development of critical thinking, creativity, and problem-solving skills, the effective use of technology, and collaboration among schools, families, and communities. Therefore, fostering adaptability and flexibility should become an integral part of the educational process in preparing students to become resilient, creative, and capable of facing the challenges of a continuously changing world.